Nativist but not alienated: A comparative perspective on the radical right vote in Western Europe. (March 2014) - Zhirkov, Kirill
In the present study I use large-scale survey data to compare radical right voting to other forms of electoral behavior in Western Europe. The chosen method, multilevel multinomial logistic regression, allows, first, distinguishing among voting for several party families as well as abstention and, second, controlling for differences between countries and survey rounds. I find that the radical right electorate is not characterized by social alienation or anti-modern values; these characteristics are more likely to be encountered among people who abstain from elections. Radical right voting is most strongly motivated by political attitudes, namely by negative perception of immigration, political mistrust, opposition to income redistribution, and – rather unexpectedly – political satisfaction. My analysis also shows that radical right parties in different West European countries attract voters with similar ideological orientations which remain relatively stable over time. In the conclusion I discuss the implications of my findings for comparative research on the radical right party family.